International humanitarian law : an anthology - Doswald-Beck, Louise; Chowdhury, Azizur Rahman; Bhuiyan, Jahid Hossain (Gurgaon : LexisNexis Butterworth Wadhwa Nagpur, 2009)
Contributed articles.
Includes bibliographical references and index.
Keywords: Humanitarian law